2002
DOI: 10.1046/j.1464-410x.2002.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving prostate cancer detection with an extended‐core transrectal ultrasonography‐guided prostate biopsy protocol

Abstract: Objective To investigate whether taking two transition zone (TZ) and four lateral peripheral zone (PZ) biopsies in addition to routine parasaggital sextant biopsies would improve detection rates in men with suspected prostate cancer. Patients and methods The study included 493 consecutive men (mean age 68.7 years, sd 8.2) with elevated serum prostate‐specific antigen (PSA) levels and/or abnormal findings on a digital rectal examination who underwent transrectal ultrasonography‐guided prostate biopsy. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 34 publications
2
57
0
2
Order By: Relevance
“…2 Protocols proposed to improve the cancer detection rate have included increasing the number of specimen cores and sampling extended fields of the prostate. 3,4 These studies indicated that useful sites to add to sextant biopsy included far lateral and anterior horn. However, Durkan et al 3 reported that 31 of 164 cancer cases (19%) were not detected by sextant biopsies, and in 17 of these 31 cases, the transition zone (TZ) biopsies alone were positive.…”
Section: Introductionmentioning
confidence: 99%
“…2 Protocols proposed to improve the cancer detection rate have included increasing the number of specimen cores and sampling extended fields of the prostate. 3,4 These studies indicated that useful sites to add to sextant biopsy included far lateral and anterior horn. However, Durkan et al 3 reported that 31 of 164 cancer cases (19%) were not detected by sextant biopsies, and in 17 of these 31 cases, the transition zone (TZ) biopsies alone were positive.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, as mathematical models have shown that sextant biopsy misses 27% of tumors, and the probability of identifying a fixed volume of prostate cancer increases by taking more cores [16] . Results from clinical studies have shown that the sextant protocol for TRUS-guided prostate biopsy can miss cancer in 19%-31% of cases [17,18] . To overcome these diagnostic shortcomings, several extended biopsy policies have been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these diagnostic shortcomings, several extended biopsy policies have been advocated. Increasing the number of cores from six to eight, with extra cores targeted along the post-lateral margins of the gland, identifies up to 20% more tumors [19] , but even an eight-core biopsy may miss cancer, and others have advocated [16,18] more biopsies per gland [20][21][22] . However, trying to improve the diagnostic accuracy should not be at the expense of the increased complication rate that may accompany more core biopsies, particularly bleeding, as occurred in our patient, especially when the prostate and surrounding rectal tissue are supplied by a rich vascular bed that consists of branches of the inferior vesicular artery and the middle and inferior rectal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…39 Several groups have published results showing higher cancer detection rates with the 5-region prostate biopsy scheme compared to standard sextant technique for primary biopsy (cores ranged from 10 to 13). 39,[43][44][45][46][47] An exhaustive systematic review of the literature of cancer detection rates with different extended prostate biopsy schemes compared to the standard sextant scheme was published by Eichler and colleagues 48 (Level 1 evidence). Eighty-seven studies were reviewed with a total of 20 698 patients.…”
Section: Extended Biopsy Schemesmentioning
confidence: 99%